PENGARUH PEMBERIAN KOTORAN BEBEK DAN POC SAYURAN PADA PERTUMBUHAN DAN PRODUKSI TOMAT BUAH ( Solanum lycopersicum L. ) - Sembiring, Gery Tarindo; Ate Tarigan, Ruth Riah; Siregar, Maimunah (Fakultas Pertanian, Universitas Janabadra, 2024)
The aim of this research was to determine the effect of applying duck manure and liquid organic vegetable fertilizer on the growth and production of tomato plants. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were required in the study. The first factor examined was the treatment of duck manure with the symbol